12. Forschungsreise des FFS "Walther Herwig" nach Westgrönland (13.11. - 18.12.1965) - Bohl, H. (1966)
Johann Heinrich von Thunen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung – Information on Fishery research in 2010